Makna dan Ekspresi Kebahagiaan di Kalangan Generasi Langgas di Kecamatan Teluk Nibung Kota Tanjungbalai - Chaliza, Nurul (UIN Sumatera Utara, 2023)
The search of the meaning of happiness began with the restlessness of the langgas generation about how to interpret the true meaning of happiness. Coupled with the challenges faced by the langgas generation, namely the flow of modernization where many humans experience disorientations loss of direction and a shift in character. Therefore, this paper knows and describes how the meaning and expression of the happiness of the langgas generation in Teluk nibung disrict, Tanjung balai city. This research through field with a qualitative method approach. The results of research in Teluk nibung disrict Tanjung balai city which focuses on understanding the meaning and expression happiness based on the views of the langgas generation happy as goals, family and relatives, stress-free living, sprituality, prosocial behavior, health, and financial.Keywords: Happiness, Langgas Generation, Meaning.